ماهية الألعاب الإلكترونية ودواعي التعلّق بها - بوخاري, فتحي; شعوة, على (جامعة الوادي - University of Eloued, 2019)
يعدّ اللعب أوّل مرحلة من مراحل تفاعل الأطفال مع البيئة المحيطة بهم، وهو جزء أساسي من حياتهم اليومية، وله دور مهمّ في نموّ جوانبهم المعرفية والانفعالية والجسمية والاجتماعية. وقد مارس الأطفال قديما ومازالوا يمارسون الألعاب الشعبية، التي تمارس في الساحات المفتوحة بعفوية وانطلاق، وهي عبارة عن تراث ثقافي ينتقل من جيل إلى جيل، وفيها يستخدم الأطفال بعض الأدوات البسيطة كالكرة أو الحبل أو الحجر وغيرها من الأدوات، وتحكم هذه الألعاب قواعد بسيطة وغير معقّدة، تجعل من السهل على جميع الأطفال المشاركة فيها. وفي السنوات الأخيرة تأثّر العالم أجمع بانفجار معرفي وتكنولوجي طال جميع جوانب الحياة، ممّا أثّر بصورة طبيعية على طريقة لعب الأطفال، وبذلك انتشرت الألعاب الإلكترونية وتطوّرت بشكل ملفت للنظر، فأصبح الأطفال يلعبون باستخدام الأجهزة الإلكترونية المتوافرة بين أيديهم وأيدي أولياء أمورهم، كالهواتف الذكية والحواسيب المحمولة والمكتبية والتلفاز وأجهزة الألعاب المتنوعة، وهو ما يجعلنا نحاول معرفة ماهية هذه الألعاب ودواعي استعمالها لدرجة الإدمان، وأنواعها الكثيرة والمتجدّدة. Play is the first stage of children's interaction with the surrounding environment, and it is an essential part of their daily life, and it has an important role in the development of their cognitive, emotional, physical and social aspects. In the past, children practiced and are still playing folk games, which are practiced in the open squares spontaneously and out, which is a cultural heritage that is transmitted from generation to generation, and in which children use some simple tools such as a ball, rope, stone and other tools, and these games are governed by simple and uncomplicated rules It makes it easy for all children to participate. In recent years, the whole world has been affected by an explosion of knowledge and technology that affected all aspects of life, which naturally affected the way children play, and thus electronic games spread and developed remarkably, so children play using electronic devices available in their hands and the hands of their parents, such as smart phones, laptops and desktops. Television and various gaming devices, which makes us try to find out what these games are and the reasons for their use to the point of addiction, and their many types and renewed
What are electronic games and the reasons to be attached to them
مقال
Keywords: الألعاب الإلكترونية ، دواعي التعلّق